Islamic Religious Education Modifies Traditional Doctrinal Instruction Into Dialogical Contextual Learning: Pendidikan Agama Islam Memodifikasi Instruksi Doktrinal Tradisional Menjadi Pembelajaran Kontekstual Dialogis - Andriyansyah Andriyansyah; Tumin Tumin (Halaqa: Islamic Education Journal, 2026)
General Background Islamic pedagogy is traditionally understood as transmitting normative doctrine. Specific Background Contemporary society is increasingly pluralistic and facing sustainability challenges, requiring a balance of communal and civic goals. Knowledge Gap Existing literature often discusses pluralism, citizenship, ecology, and digitalization separately, lacking an integrative synthesis. Aims This Systematic Literature Review synthesizes the integration of the Sustainable Development Goals within faith-based learning using the PRISMA framework. Results Analysis of 34 Scopus-indexed articles from 2020 to 2026 reveals a shift from doctrinal models toward multidimensional instruction. Faith-based learning functions as an integrative space forming tolerant, critical, and environmentally careful learners. Furthermore, the concept of adab serves as the crucial link connecting normative values with sustainability orientations. Novelty This research establishes a unified conceptual relationship placing pedagogy as a multidimensional system that simultaneously addresses faith, ecological responsibility, and digital literacy. Implications Integrating these dimensions positions sustainable pedagogy as highly relevant to contemporary challenges, requiring shifts towards reflective teaching and the development of teachers' competencies. Highlights The concept of adab connects faith values with sustainability orientations. Integrating the SDGs promotes tolerant students possessing critical thinking abilities. Cultivating ecological responsibility and digital literacy prepares citizens for contemporary challenges. Keywords Islamic Religious Education; Sustainable Development Goals; Ecological Citizenship; Digital Literacy; The Concept Of Adab